THE EFFECT OF USING POSTER MEDIA ON THE ABILITY TO WRITE DESCRIPTIVE ESSAYS FOR IV GRADE STUDENTS AT SD NEGERI 141 PEKANBARU - Nikita Ayu Andani (Yayasan Thaifah Manshurah Pekanbaru, 2022)
This article discusses the results of students' ability in writing descriptive essays which are still low. The purpose of this study was to determine the effect of using poster media on the ability to write descriptive essays for fourth grade students of SD Negeri 141 Pekanbaru. The research method used is a quasi-experimental method with a non-aquivalent randomized pretest posttest design. The sample of this study involved 60 students who were divided into 2 classes, namely the experimental class and the control class. Data collection techniques using observation, tests, and documentation. To find out the students' initial abilities, they did a pretest in each of the two groups, while to find out the students' final abilities, they did a posttest in both groups. From the two tests that have been carried out, it was found that the average increase in the pretest posttest was 21,95 for ,the experimental class while the control class was 4,70. Normality and homogeneity tests were also carried out by obtaining a significance value > 0.05, it means that the data is normal and homogeneous. Hypothesis testing was obtained with a significance value of 0.024 <0.05, so it can be concluded that there is an influence from the use of poster media on the ability to write descriptive essays for fourth grade students of SD Negeri 141 Pekanbaru.